Implementasi Rencana Induk Pengembangan Kawasan Sentul City Terhadap Limpasan Puncak dan Konstribusi Banjir - Asep Suheri; Cecep Kusmana; Moh Yanuar J Purwanto (TATALOKA, 2021)
The purpose of this study is to create a peak runoff model in urban SC areas based on existing land use/land cover (LU / LC) and a master plan. To calculate peak runoff (PRO) using the rational method. To find out the current LU / LC through existing SPOT-6 image analysis in 2017, using supervised classification method with an estimation of gamma distribution parameters with the maximum likelihood method using QGIS 2.8 software, SAGA GIS, and Arc -GIS 10.4.1. Based on the results of image analysis obtained twelve types of LU, which can be grouped into three types of LC, namely 33% of developed land, 65% of vegetated land (RTH), and 2% of blue open land (RTB). The analysis shows that the implementation of the master plan increases PRO. With the increase in PRO will contribute to flooding in the downstream areas, consequently the developer must be responsible for reducing the PRO.